Defining the specificity of recombinant human erythropoietin confirmation in equine samples by liquid chromatography‐tandem mass spectrometry. Issue 4 (21st December 2021) - Timms, Mark; Steel, Rohan
Abstract: The proteotypic human EPO peptides YLLEAK (T4), SLTTLLR (T11), TITADTFR (T14), and VYSNFLR (T17) are often used to confirm the presence of recombinant human EPO (rhEPO) in equine samples. Each of these peptides contains one or more isomeric leucine or isoleucine amino acids, raising the possibility that a simple leucine/isoleucine substitution could lead to a false identification when compared with a rhEPO reference standard. To examine this possibility variants of these four peptides were analysed by liquid chromatography–tandem mass spectrometry (LC‐MS/MS). These studies indicate that confirmation of rhEPO in equine samples by immuno‐affinity capture and LC‐MS/MS analysis is true and accurate. It was also found that chromatography played a greater role in determining LC‐MS/MS specificity than tandem mass spectrometry and that, in the case of more hydrophilic peptides, the accuracy of peptide identification could be enhanced by the inclusion of 13 C and 15 N labelled peptide internal standards. Abstract : Synthetic peptides were used to investigate the specificity of rhEPO confirmation by LC‐MS/MS. Immunoaffinity purification and chromatography was more important for specificity than tandem mass spectrometry.